Influence of IMF‐By on the Equatorial Ionospheric Plasma Drifts: TIEGCM Simulations. Issue 9 (31st August 2021) - Hui, Debrup; Vichare, Geeta
Abstract: The influence of east‐west component of interplanetary magnetic field (IMF‐By) on ionospheric plasma convection over polar region is well established by both observation and modeling studies. However, its influence beyond polar latitudes has rarely been addressed. To understand the effects of IMF‐By at low‐latitudes during geomagnetic storm times, we have designed simulation experiments using Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model. This communication shows that strong IMF‐By and its polarity has effects on the storm‐time ionosphere‐thermosphere dynamics even near equator. It can change zonal electric field, magnitude of morning/evening time pre‐reversal‐enhancements (PRE) and meridional winds. At the storm onset when prompt penetration electric fields prevail, a strong IMF‐By, in general, reduces the vertical plasma drifts over the equator and the largest effects are observed near sunrise and sunset terminators. Later when disturbance dynamo is active, morning PRE appears, and a strongly positive IMF‐By strengthens morning PRE and weakens evening PRE, with respect to zero IMF‐By conditions. A strongly negative IMF‐By just shows the reverse, thus indicates dawn‐dusk asymmetry due to IMF‐By. It is also seen that the meridional winds are oppositely directed during positive and negative IMF‐By conditions. The effects of IMF‐By transition are observed on the evening PRE within 2 h from the transition. The new insights successfully explain the observations from a few earlier available works. However, the presented results should be treated with caution in view of model limitations associated with the empirical patterns of high latitude convection and preliminary scheme of merging high latitude‐low latitude potentials. Plain Language Summary: Storm time reconnection results in exchange of huge amount of momentum, energy and particles, which causes changes in the Earth's ionosphere‐thermosphere system. When the primary driver north‐south component of interplanetary magnetic field (IMF‐Bz), controls this flow of energy and particles, east‐west component of interplanetary magnetic field (IMF‐By) modulates this flow thereby altering the impacts on the Earth's ionosphere during geomagnetic storm evolution. Our knowledge about this modulation is limited to polar regions only, where it is quite pronounced. The impact of IMF‐By beyond polar ionosphere is sparse and has rarely been reported. This is because of the masking of its influence by the overwhelming effects of IMF‐Bz. In this study, special experiments are designed using Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model to understand the impact of IMF‐By on ionosphere near equator, during storm times. It is found that a strong IMF‐By during geomagnetic storm and its polarity can substantially influence the plasma convection up to equatorial latitudes and alter the neutral dynamics as well. A reliable space weather forecasting must incorporate the effects of IMF‐By. Key Points: East‐west component of interplanetary magnetic field (IMF‐By) affects the ionospheric electrodynamics beyond polar latitudes even near equator, during southward IMF A strong IMF‐By reduces prompt penetration electric field near equator, and the effects are stronger near sunset and sunrise terminators Role of IMF‐By polarity is seen during disturbance dynamo, giving dawn‐dusk asymmetry; meridional wind reverses on IMF‐By polarity reversal